THE CONCEPT OF TAZKIYATUN NAFS WITHIN ISLAMIC GUIDANCE AND COUNSELING: A SPIRITUAL FRAMEWORK FOR UNDERSTANDING MENTAL HEALTH - Sholihuddin (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
This study investigates the effectiveness of Tazkiyatun Nafs as a spiritual framework within Islamic counseling for addressing mild to moderate mental health disorders. Adopting a descriptive qualitative design, data were obtained through in-depth interviews and an extensive literature review, then analyzed using thematic content analysis. The findings reveal that the sequential stages of Takhalli, Tahalli, and Tajalli substantially facilitate participants’ emotional regulation, self-reflection, and spiritual awareness. These outcomes contribute to the theoretical advancement of Sufi-oriented Islamic counseling and highlight the potential for integrating this approach into Islamic psychological education and therapeutic practice. The study recommends the development of counselor training programs based on Tazkiyah principles and further empirical investigation involving broader populations and diversified methodologies to enhance the model’s validity and applicability.